ABU ZAYD AL-BALKHI'S PERSPECTIVE ON DEPRESSION AND ANXIETY IN 'MASALIH AL-ABDAN WA AL-ANFUS' - Raudah, Shalawati Fi; Arief, Yanwar; Rahman, Azhar Abdul (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2023)
Abu Zayd al-Balkhi was a Muslim polymath who made significant contributions to the field of psychology, particularly in his views on depression and anxiety. This research aims to comprehend al-Balkhi’s perspective on depression and anxiety in the context of Islam during his time and to contribute to the understanding of mental health that aligns with Islamic values. The study employs a literature research method to analyze his main work, “Masalih al-Abdan wa al-Anfus”, and investigates al-Balkhi’s opinions on depression and anxiety. Researchers also classify different types of depression and the understanding of anxiety as proposed by al-Balkhi. The research findings reveal that al-Balkhi was one of the early pioneers in understanding mental disorders by categorizing psychological symptoms within a more modern framework. Furthermore, the study highlights his views on the connection between physical and mental health and emphasizes the significance of maintaining a balance between the two.